"EFFECT OF DIFFERENT SALICYLIC ACID CONCENTRATIONS ON GUGGULSTERONE Z BIOSYNTHESIS IN COMMIPHORA WIGHTII" - Aditi Panpalia1, Khushbu Verma* (Chelonian Research Foundation, 2023)
Salicylic acid is an elicitor that has been widely used to enhance the production of secondary metabolites in plants. In this context, the present study aims to investigate the effect of salicylic acid on the production of Guggulsterone Z in the Guggul plant (Commiphora wightii). Guggulsterone Z is a bioactive compound with potent anti-inflammatory and cholesterollowering properties, which makes it a valuable pharmaceutical compound. In this study, the Guggul plant was treated with different concentrations of salicylic acid. The results showed that the application of salicylic acid significantly elevated the Guggulsterone Z content in the Guggul plant, with the optimal concentration being 100 µm. The findings of this study provide valuable insights into the use of salicylic acid as an elicitor for enhancing the production of Guggulsterone Z of the Guggul plant. Keywords:- Salicyclic acid, Guggulsterone Z, Guggul plant (Commiphora wightii)